Nutrient addition alters plant community productivity but not the species diversity of a mountain meadow in Tajikistan - Mekhrovar, Okhonniyozov; Li, Yao-ming; Abdullo, Madaminov; Sino, Yusupov; Fan, Lianlian (Frontiers in Plant Science, 2024)
Tajikistan is a typical mountainous country covered by different mountain grasslands that are important pasture resources. Recently, grassland degradation has become widespread due to climate change and human activities and fertilization has been used to improve grassland production. However, fertilizer inputs can substantially alter species diversity, but it is unclear how productivity and species diversity respond to nutrient enrichment in the mountain meadows of Tajikistan. Therefore, a 5-year (2018–2022) continuous in-situ mineral fertilizer experiment was conducted to examine the effects of three nitrogen (N) levels (0, 30, and 90 kg N ha–1 year–1), two phosphorus (P) levels (0 and 30 kg P ha–1 year–1), and their combinations on above-ground biomass (AGB) and species diversity in a mountain meadow grassland in Ziddi, Varzob region, Tajikistan. Five species diversity metrics—Margalef’s species richness, the Shannon–Wiener index, the Simpson index, Pielou’s equitability index, and the Evar Species Evenness index—were used to measure species diversity. The results indicated that the addition of different N and P amounts and their various combinations considerably increased both total and dominant species AGB, with the highest increase occurring in the N90P30 (90 kg N ha–1 year–1 combined with 30 kg P ha–1 year–1) treatment in 2022; during the experiment, the importance value of Prangos pabularia (dominant species) first decreased and then increased, but its dominant status did not change or fluctuate among the years. Furthermore, N, P, and their different combinations had no significant effect on species diversity. All the species diversity indexes fluctuated among years, but there was no interaction with mineral fertilizer addition. Total AGB had a negative relationship with species diversity and low concentration N fertilizer addition (N30; P30) strengthened this negative trend. However, this trend decreased under the high N fertilizer condition (N90P30). Overall, nutrient addition to the natural mountain grassland of the Varzob region improved AGB, which meant that there was more forage for local animals. Mineral fertilizers had no significant effect on species diversity, but may enhance P. pabularia dominance in the future, which will help maintain the stability of the plant community and improve the quality of the forage.